2010
DOI: 10.5114/aoms.2010.14469
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right atrial and right ventricular size in children after percutaneous closure of secundum atrial septal defect with Amplatzer septal occlude

Abstract: IntroductionThe aim of this study was to evaluate the right atrial (RA) and right ventricular (RV) size, and the speed of their normalization, in children after percutaneous closure of secundum atrial septal defect with the Amplatzer septal occluder.Material and methodsThe study group consisted of 42 children, aged 4.5 to 18.5 years. The following measurements (indexed to body surface area) were performed using 2D echocardiography: longitudinal, transverse axis and area of RA, RV inflow dimensions at one-third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…[ 20 , 21 ] Other investigators have reported results of echocardiography during postoperative follow-up of patients who have undergone percutaneous closure of ASD. [ 22 24 ] Eroglu et al concluded that percutaneous closure results in rapid remodeling and normalization of RV deformation, and the major geometrical and deformational changes are completed in 24 hours. [ 25 ] Takaya et al reported that cardiac remodeling and exercise capacity could be improved over a long-term period after transcatheter closure of ASD in middle-aged and elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 , 21 ] Other investigators have reported results of echocardiography during postoperative follow-up of patients who have undergone percutaneous closure of ASD. [ 22 24 ] Eroglu et al concluded that percutaneous closure results in rapid remodeling and normalization of RV deformation, and the major geometrical and deformational changes are completed in 24 hours. [ 25 ] Takaya et al reported that cardiac remodeling and exercise capacity could be improved over a long-term period after transcatheter closure of ASD in middle-aged and elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the young age and small BSA had a positive impact on GLS and RV free wall LS beside the impact of ASD, which was significantly higher in children and adolescents [27]. Generally, the BSA has a significant impact on echocardiographic parameters of growing ages than adults [26,28]. Table 4 Comparison between LV and RV GLSS and RV free wall LS before, after 24 h and 1 month of transcatheter ASD closure in relation to the controls Pvalue1: Comparison of ASD data (Pre-closure, 24 h and 1 month Post-closure) versus controls Pvalue2: ASD data (24 h and 1 month Post-closure) in comparison with Pre-closure Pvalue3: ASD data (1 month after closure) in comparison with 24 h Post-closure Continues data were presented as mean ± SEM.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, there are some confounding factors that had impact on some baseline echocardiographic parameters, such as the positive impact of BSA and age on TAPSE to result in progressive increase in TAPSE values with adulthood and increased BSA [ 25 ]. However, the inverse relation between the BSA of underweighted ASD children and adolescents was responsible for the exaggerated impact of ASD on increasing the indexed right-sided dimensions to BSA before the time of closure [ 26 ]. Moreover, the young age and small BSA had a positive impact on GLS and RV free wall LS beside the impact of ASD, which was significantly higher in children and adolescents [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of right heart enlargement from Transthoracic Echocardiography (TTE) can be used as an indication of ASD closure [4,9]. Volume overload of the right atrium (RA) and right ventricle (RV) is known to be a consequence of the condition of untreated ASD, and the presence of persistent shunting can have an effect on the appearance of cardiac arrythmias [10].…”
Section: Introductionmentioning
confidence: 99%